RNA epigenetic modifications in digestive tract cancers: Friends or foes - Zekai Nian; Ming Deng; Lele Ye; Xinya Tong; Yixi Xu; Yiliu Xu; Ruoyao Chen; Yulin Wang; Feiyang Mao; Chenyv Xu; Ruonan Lu; Yicheng Mao; et al. (Elsevier, 2024)
Digestive tract cancers are among the most common malignancies worldwide and have high incidence and mortality rates. Thus, the discovery of more effective diagnostic and therapeutic targets is urgently required. The development of technologies to accurately detect RNA modification has led to the identification of numerous RNA chemical modifications in humans (epitranscriptomics) that are involved in the occurrence and development of digestive tract cancers. RNA modifications can cooperatively regulate gene expression to facilitate normal physiological functions of the digestive system. However, the dysfunction of relevant RNA-modifying enzymes ("writers," "erasers," and "readers") can lead to the development of digestive tract cancers. Consequently, targeting dysregulated enzyme activity could represent a potent therapeutic strategy for the treatment of digestive tract cancers. In this review, we summarize the most widely studied roles and mechanisms of RNA modifications (m6A, m1A, m5C, m7G, A-to-I editing, pseudouridine [Ψ]) in relation to digestive tract cancers, highlight the crosstalk between RNA modifications, and discuss their roles in the interactions between the digestive system and microbiota during carcinogenesis. The clinical significance of novel therapeutic methods based on RNA-modifying enzymes is also discussed. This review will help guide future research into digestive tract cancers that are resistant to current therapeutics.